Mathematical modeling of Zika disease in pregnant women and newborns with microcephaly in Brazil - Ndairou, Faiçal (2018)
We propose a new mathematical model for the spread of Zika virus. Special attention is paid to the transmission of microcephaly. Numerical simulations show the accuracy of the model with respect to the Zika outbreak occurred in Brazil.